2021
DOI: 10.1021/acsami.1c06309
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Antiagglomerant Performance with Gas Hydrate Cohesion

Abstract: Although inhibiting hydrate formation in hydrocarbon− water systems is paramount in preventing pipe blockage in hydrocarbon transport systems, the molecular mechanisms responsible for antiagglomerant (AA) performance are not completely understood. To better understand why macroscopic performance is affected by apparently small changes in the AA molecular structure, we perform molecular dynamics simulations. We quantify the cohesion energy between two gas hydrate nanoparticles dispersed in liquid hydrocarbons i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Recent simulations have considered the role of QLL in the adsorption of LDHIs. In particular, Sicard et al 156 and Phan et al 157 simulated a 0.5 nmthick QLL by depositing liquid water molecules on hydrate surfaces to study the effects of LDHIs on the aggregation of hydrate particles in a model hydrocarbon (Figure 13).…”
Section: ■ Applications In Sustainable Technologiesmentioning
confidence: 99%
“…Recent simulations have considered the role of QLL in the adsorption of LDHIs. In particular, Sicard et al 156 and Phan et al 157 simulated a 0.5 nmthick QLL by depositing liquid water molecules on hydrate surfaces to study the effects of LDHIs on the aggregation of hydrate particles in a model hydrocarbon (Figure 13).…”
Section: ■ Applications In Sustainable Technologiesmentioning
confidence: 99%
“…Some hydrate antiagglomeration hypotheses have been proposed, for example, adsorption of AAs to hydrate particles may weaken the cohesive forces between particles or even induce strong repulsion forces among particles or inhibit hydrate growth by covering the hydrate surface with AA molecules; antiagglomeration of hydrate particles may be closely related to the change in the surface free energy of the hydrate and that the hydrate surface became lipophilic with the adsorption of AAs . The Striolo group has performed several molecular dynamics (MD) simulation studies to reveal the structure–performance relation for surfactants as model AAs; ,, specifically, the effects of headgroups, hydrophobic tail lengths, and structural rigidity of surfactants and surfactant packing density on the hydrate surface on the ability to prevent hydrate coalescence. These simulation studies , also observed that the thin film of AAs adsorbed at water/oil or hydrate/oil interfaces could delay hydrate formation by imposing a barrier for CH 4 transport.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the experimental results, they obtained a new anti-coagulation mechanism of emulsion-free hydrates based on micelle equilibrium. Phan et al (Phan et al 2021) aimed to accurately predict and design the molecular structure and properties of the Anti-agglomerants agent by simulation method. They compared the kinetic simulation data with the experimental data of micromechanical force measurement and obtained good consistency.…”
Section: Introductionmentioning
confidence: 99%